The sorta sisters - Fogelin, Adrian (Peachtree, 2007)
In Florida, Anna Casey lives with what she hopes is the last in a long line of foster mothers, and Mica Delano lives with her father on their small boat, and when the two of them begin corresponding, they discover they have a lot in common